Electronic properties of tantalum pentoxide polymorphs from first-principles calculations - Lee, J.; Lu, W.; Kioupakis, E. (Applied physics letters, 2014)
Tantalum pentoxide (Ta2O5) is extensively studied for its attractive properties in dielectric films, anti-reflection coatings, and resistive switching memory. Although various crystalline structures of tantalum pentoxide have been reported, its structural, electronic, and optical properties still remain a subject of research. We investigate the electronic and optical properties of crystalline and amorphous Ta2O5 structures using first-principles calculations based on density functional theory and the GW method. The calculated band gaps of the crystalline structures are too small to explain the experimental measurements, but the amorphous structure exhibits a strong exciton binding energy and an optical band gap (∼4 eV) in agreement with experiment. We determine the atomic orbitals that constitute the conduction band for each polymorph and analyze the dependence of the band gap on the atomic geometry. Our results establish the connection between the underlying structure and the electronic and optical properties of Ta2O5.